Mapeamento das pesquisas em educação matemática Inclusiva: a partir da criação e atuação do GT13 no SIPEM da SBEM - Silva, Viviane Regina de Oliveira (2020)
This research presents a survey about what has been discussed about the inclusion of people with disabilities in the Education area, highlighting their relevance and contributions to the teaching of Mathematics Education. Its objective was to map the articles presented in the Working Group (WG) 13 Difference, Inclusion and Mathematical Education and to survey which thematic focuses, institutions involved and the regions to which they belong, as well as to verify if these works allow to analyze how the process occurs inclusion of children with hearing impairment in the school environment, since 48% of published academic productions address issues related to students with this disability. The theoretical contribution to this investigation was based on the contributions of Fernandes (2011) and the methodological foundation was centered on the studies by Bardin (2011). To this end, we carried out a mapping of the research presented in the GT 13, in the events of the International Research Seminar in Mathematical Education (SIPEM) promoted by the Brazilian Society of Mathematical Education (SBEM) and semi-structured interview with the group's coordination. That said, we observed that 95% of published research was carried out in Brazil, with a contingent of 63% by institutions located in the southeast region. After the respective mapping, we identified that the analyzed works reveal the need for teacher training courses that work in inclusive education and that the reports, experiences and discussions are still under initial debate among researchers, so that it was not possible to structure the process inclusion of deaf or hearing impaired students. We also concluded that it was not possible to answer all the questions that led this research, however, we reinforce the importance of the researcher's role in this process.